ANALISIS KUALITAS LAYANAN DALAM UPAYA PENINGKATAN KEPUASAN PELANGGAN DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (IPA) DI BATIQA HOTEL PEKANBARU - Aldi Ramadhanil Gamma; Samsir Samsir; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the gap between performance and customer expectations for service quality, knowing the attributes that are priority to improve service quality, as well as efforts to improve service attributes at Batiqa Hotel Pekanbaru. The population in this study were all customers who visited Batiqa Hotel Pekanbaru. The sample selection was carried out using purposive sampling method, while the number of samples in this study amounted to 100 respondents. The data used in this study are primary and secondary data. Primary data were collected using a questionnaire as an instrument to prove the results of the research, the data were processed using the Servqual method and the Importance Performance Analysis (IPA) methodKeywords: Service Quality, Servqual, IPA